(untitled) (Pedagogy of Higher and Secondary Education, 2022)
Forming intellectual ability demands special conditions which helps child to overcome stresses, overstrain, uneasness, schools, fears, connected with the process o f teaching which contributes to propitious climate for fitted developing of pupils personality in the primary school.